2018
DOI: 10.15405/epsbs.2018.11.02.8
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors Of Creative Writing At Age 9

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…As the present study shows, creative content in writing can be detected in primary education. As was reported in three previous studies, based partly on the same sample as the present study, a two‐componential structure emerged among the ten story dimensions (Badini et al., 2018; Toivainen et al., 2018; Toivainen et al., 2017). Five dimensions (Liking, Novelty, Imagination, Emotion, and Detail) loaded highly on the Creative Expressiveness component with creativity.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…As the present study shows, creative content in writing can be detected in primary education. As was reported in three previous studies, based partly on the same sample as the present study, a two‐componential structure emerged among the ten story dimensions (Badini et al., 2018; Toivainen et al., 2018; Toivainen et al., 2017). Five dimensions (Liking, Novelty, Imagination, Emotion, and Detail) loaded highly on the Creative Expressiveness component with creativity.…”
Section: Discussionsupporting
confidence: 86%
“…The use of the CAT has demonstrated that people can recognize and agree upon creativity even though it may be difficult to define and characterize (Hennessey, 2010). In developmental samples, the CAT has been used to evaluate creativity of musical compositions, drawings and poems (Baer, 2014; Baer, Kaufman, & Gentile, 2004; Hickey, 2001; Lubart, Pacteau, Jacquet, & Caroff, 2010), as well as children’s oral and written stories (Badini, Toivainen, Oliver, & Kovas, 2018; Hennessey & Amabile, 1988; Toivainen, Malanchini, Oliver, & Kovas, 2017). The use of the CAT to evaluate creativity in children’s written stories was piloted in three previous studies (Badini et al., 2018; Toivainen et al., 2017, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zettler (2011) posited that Machiavellians are very results-oriented and determined to pursue their goals (Career Commitment), then Brunel (2008) also found that narcissists are good at creating and taking advantage of opportunities and psychopaths can achieve high social status, being recognized as intelligent and charismatic leaders. Research Dark Triad which is attributed to the behavior of educators once done by Badini (2018) who found that Machiavellianism was a dominating personality among university teachers.…”
Section: Introductionmentioning
confidence: 99%